2016
DOI: 10.4274/jcrpe.2284
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Active Video-Accompanied Exercises in Improvement of the Obese State in Children: A Prospective Study from Turkey

Abstract: Objective:The aim of this study was to determine the effects of active video games and music-accompanied aerobic and callisthenic exercises on body mass index (BMI), body fat ratio, physical performance tests, psychosocial status, and self-respect in overweight and obese adolescents.Methods:Fifty (21 males and 29 females) slightly overweight and obese participants with no chronic disorder and of an average age of 12.16±0.99 years were included in the study. The percentile values for BMI, triceps skinfold thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 23 publications
1
18
1
1
Order By: Relevance
“…The Childhood Depression Inventory was used in two studies. 26,44 Interventions. Regarding the characteristics of the interventions, we observed differences between the studies (Table 2).…”
Section: Description Of Studies Included In the Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The Childhood Depression Inventory was used in two studies. 26,44 Interventions. Regarding the characteristics of the interventions, we observed differences between the studies (Table 2).…”
Section: Description Of Studies Included In the Reviewmentioning
confidence: 99%
“…Three studies compared exergames with control groups 27,42,43 and six studies compared the preintervention moment with the postintervention moment. 26,27,[42][43][44][45] The intervention period varied from studies that used 1 16,46 to 100 sessions. 42,47 Thus, the protocol was categorized into short (interventions with up to 10 sessions) and long (interventions with 24 sessions or more).…”
Section: Description Of Studies Included In the Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, on effects on mental health, other studies have shown improvement in body image [29], psychological wellbeing [30][31][32], and self-efficacy [18]. The implications related to psychological health also indicate improvements in self-esteem [33,34] and mood states [16].…”
Section: Introductionmentioning
confidence: 98%